The Effect of Ethnic Clustering on Migrant Integration in Germany - Barbara Treude (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Even though ethnic clustering is common, both economic theory and empirical research have not been able to provide a clear-cut answer on its effects on the integration of immigrants. In this paper, we study the effect of residential clustering on the labour market outcome of immigrants in Germany. Thereby, we use two measures for labour market integration: the employment probability and the wage levels. Our paper contributes to the existing literature twofold: First, we extend it to Germany on which hardly any research has been conducted. Second, we employ a new methodological approach which allows for the identification of smaller ethnic clusters and thus a more precise estimation of its effects. This is achieved by including neighbouring spatial units in the regression model. In order to control for the endogeneity of the location decision, we use a two-step strategy, combining a control function and an instrumental variable (IV) approach. We observe immigrant clustering in Germany, using a Moran s I analysis. In addition, the analysis suggests the importance of residential clustering for the employment probability of immigrants, and for second or higher generation migrants, a positive impact of clustering on wages.
Keywords: J61; J31; R23; 330